2014
DOI: 10.1016/j.jval.2014.08.2111
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Burn Care: A Systematic Review

Abstract: Objectives: Chronic idiopathic (or spontaneous) urticaria (CIU) is estimated to occur in 0.3% of the general population in Turkey. Although the burden of the disease is substantial for the payer, there has been no cost-analysis performed in our country. The purposes of this study are to determine the resources and costs related to the diagnosis and treatment of patients with CIU, and to estimate the annual economic burden to the Social Security Institution (SGK). MethOds: Delphi technique was applied to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 0 publications
3
29
1
Order By: Relevance
“…The events that occur during the proliferative phase include angiogenesis, deposition of collagen, epithelialization, and wound contraction [20,21]. Burn healing occurs by secondary intention, a slow process with a high infection risk and produces scar retraction, which may lead to extensive scarring and subsequent high burn-related treatment costs, depending on the injury location [22]. This study demonstrated in vivo clinical effects of low-level laser therapy (LLLT) on second-degree thermal burns in rats.…”
Section: Discussionmentioning
confidence: 84%
“…The events that occur during the proliferative phase include angiogenesis, deposition of collagen, epithelialization, and wound contraction [20,21]. Burn healing occurs by secondary intention, a slow process with a high infection risk and produces scar retraction, which may lead to extensive scarring and subsequent high burn-related treatment costs, depending on the injury location [22]. This study demonstrated in vivo clinical effects of low-level laser therapy (LLLT) on second-degree thermal burns in rats.…”
Section: Discussionmentioning
confidence: 84%
“…Burns dressings are expensive and with a large number of children treated for burns every year, this is a significant burden on the healthcare system [18]. A systematic review of burn care costs calculated the mean total cost as $3,883 per 1% TBSA burned for burns 0-10% TBSA in high income countries [18].…”
Section: Treatmentmentioning
confidence: 99%
“…Burns dressings are expensive and with a large number of children treated for burns every year, this is a significant burden on the healthcare system [18]. A systematic review of burn care costs calculated the mean total cost as $3,883 per 1% TBSA burned for burns 0-10% TBSA in high income countries [18]. As a comparison to other morbidities, a study on burn care in Spain reported that the mean annual cost of burn care was $99,773 compared to $13,826 in the first year post-stroke for stroke survivors [19].…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations